EVALUASI PROGRAM PENCEGAHAN DAN PENGENDALIAN TUBERKULOSIS DI PUSKESMAS SEI AGUL TAHUN 2022 - Chairunnisa, Chairunnisa (Jurnal Kajian Kesehatan Masyarakat, 2025)
Program evaluation is conducted to determine the level of success of a program by knowing the effectiveness of each component. This study aims to evaluate gaps in the implementation of the Tuberculosis Prevention and Control program at Sei Agul Health Center in 2022. This type of research is qualitative research with descriptive methods. The informants of this study were the Head of Puskesmas, TB program holder, cadre, DM program manager, HIV program manager, MCH program manager. The results showed that there are still gaps in health promotion, case finding, risk factor control, resources, coordination, networking and partnerships and in community participation. Suggestions include collaborating with health promotion program holders to disseminate information and TB control program activities that have been carried out to social media and local TV. Involve community leaders, religious leaders, influencers and testimonials of former TB patients by creating interesting content, using local language that is easy to understand and uploaded on the official accounts of the Medan City Health Office and puskesmas either on tiktok, instagram or facebook. Conduct training/workshops for DM, HIV and MCH program holders on TB screening in patients who have risk factors for comorbidities, create quarterly TB case finding achievement charts for puskesmas and conduct continuous socialization, implement a public private mix program between hospitals, clinics, puskesmas and other health worker practices to implement the TB DOTS program.